Microelement strontium and human health: comprehensive analysis of the role in inflammation and non-communicable diseases (NCDs) - Ru, Xin; Yang, Lida; Shen, Guohui; Wang, Kunzhen; Xu, Zihan; Bian, Wenbo; Zhu, Wenqi; Guo, Yanzhi (Frontiers in Chemistry, 2024)
Strontium (Sr), a trace element with a long history and a significant presence in the Earth’s crust, plays a critical yet often overlooked role in various biological processes affecting human health. This comprehensive review explores the multifaceted implications of Sr, especially in the context of non-communicable diseases (NCDs) such as cardiovascular diseases, osteoporosis, hypertension, and diabetes mellitus. Sr is predominantly acquired through diet and water and has shown promise as a clinical marker for calcium absorption studies. It contributes to the mitigation of several NCDs by inhibiting oxidative stress, showcasing antioxidant properties, and suppressing inflammatory cytokines. The review delves deep into the mechanisms through which Sr interacts with human physiology, emphasizing its uptake, metabolism, and potential to prevent chronic conditions. Despite its apparent benefits in managing bone fractures, hypertension, and diabetes, current research on Sr’s role in human health is not exhaustive. The review underscores the need for more comprehensive studies to solidify Sr’s beneficial associations and address the gaps in understanding Sr intake and its optimal levels for human health.